ANALISIS DAYASAING DAN STRATEGI PENGEMBANGAN AGRIBISNIS KOPI INDONESIA - Sari Narulita; Ratna Winandi; Siti Jahroh (Jurnal Agribisnis Indonesia, 2014)
Indonesia is the third largest coffee exporter in the world after Vietnam. In addition to be used as an export commodity, coffee is also grown in the country. In today's era of trade globalization, competition is getting tougher conditions, where individual countries to open their markets to each other. Based on that need to be analyzed competitiveness and the development of Indonesian coffee agribusiness. Competitiveness analysis is performed by means of comparative advantage analysis of Revealed Comparative Advantage (RCA) and a competitive advantage with Porter's Diamond theory approach. The results showed that Indonesian coffee has a competitive advantage both comparative and competitive. The analysis used to generate agribusiness development strategy is the SWOT analysis tool (Strengths, Weaknesses, Opportunities and Threats). Strategy resulting from the analysis is more directed to the technical aspect and cultivation.